The Development of an Intramuscular Injection Simulation Pad Innovation - Laowprachawit, Kletkaew; prommul, jirarat; Aitsaro, Charuwan; Chuklang, Chirarat; Jitbanjong, Jutalak; Phokwan, Chatwadee (Princess of Naradhiwas University Journal, 2025)
The purposes of this research and development of innovation were to develop a muscle injection simulation pad and study its effectiveness. The research was conducted in two steps: Step 1: Development of the muscle injection simulation pad, which included 1) studying the situation of muscle injections, theoretical concepts, related research, and experts; 2) developing the innovation; and 3) testing the innovation. Step 2: Evaluating the effectiveness of the innovation. The sample group consisted of 27 third-year nursing students, generation 57, Boromarajonani College of Nursing, Songkhla, academic year 2024. The research instruments included 1) the muscle injection simulation pad and 2) the effectiveness assessment form for the muscle injection simulation pad. The content validity index (CVI) was 0.71, and the Cronbach's alpha coefficient was 0.92. Data were analyzed using mean, standard deviation, frequency, and percentage. The research findings were revealed as detailed below. 1. An intramuscular injection simulation pad innovation: The surface texture of the skin layer allowed for easy needle penetration. It was soft. It has clearly defined color separation between the muscle layers. It can inject fluids and extract air realistically. It was reusable, and it had a long lifespan, averaging 100 baht per piece. 2. The overall effectiveness of the intramuscular injection simulation pad innovation was at the highest level (M = 4.46, S.D. = 0.65). Considering the details, it was found that the design of the structure and the practical application aspects were rated the highest (M = 4.37, S.D. = 0.50) and(M = 4.57, S.D. = 0.47), respectively. Therefore, the intramuscular injection simulation pad innovation can be used in both theoretical and practical nursing education, as the model has realistic characteristics in terms of texture, color, thickness, and skin layer.